Analisis Kelayakan Usaha Depot Air Minum Isi Ulang di Kecamatan Mulyorejo Kota Surabaya - Dyah Ayu Puspita; Joko Priyono (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
The purpose of this study is to examine the profitability and viability of refill drinking water depot enterprises in Surabaya City's Mulyorejo District. Six businesspeople who refill drinking water in the Mulyorejo District of Surabaya City served as informants for this study. In this study, total costs, sales, profits, and business viability were employed as analytical techniques. The average total expenses incurred, the average income generated, and the average profit from the research were IDR 4,544.660, IDR 9,869.167, and IDR 5,324.507. The average value of the R/C ratio is 2.14 > 1, according to the findings of calculating the three business feasibility metrics for six refill drinking water entrepreneur informants in Mulyorejo District, Surabaya City. the average B/C value The obtained ratio was 1.14 > 0. Additionally, the ROI value averaged 17,35% > 1%. Thus, the Mulyorejo District, Surabaya City drinking water replenishment business can generate enough revenue to make it worthwhile to operate.